Formulation and Activity Test of Anti-Acne Toner Containing Lemongrass Essential Oil (Cymbopogon nardus) against Propionibacterium acnes Bacteria - Wijayanti, Devi Nur; Permata, Bangkit Riska; Artini, Kusumaningtyas Siwi (Yayasan Ahmad Mansyur Nasirah, 2025)
Acne (Acne vulgaris) is caused by colonization of Propionibacterium acnes bacteria on the skin. The use of natural ingredients with antimicrobial activity for acne medication is an attractive alternative because it is considered safer than chemical ingredients. Lemongrass shows antibacterial activity. Lemongrass acne gel preparations can inhibit the growth of Propionibacterium acnes bacteria. This study aims to formulate the preparation and antibacterial activity of lemongrass essential oil toner. The method used is an experimental method. Variations in the concentration of lemongrass essential oil (Cymbopogon nardus) were tested at 10%, 20%, and 30%. The essential oil was produced using steam distillation. The physical quality of the toner formulation was tested using organoleptic testing, homogeneity testing, pH testing, and viscosity testing. This was followed by irritation testing, hedonic testing, and antibacterial activity testing of the toner formulation. Data analysis was performed using One-way ANOVA and Post Hoc. The acne-fighting toner based on lemongrass essential oil exhibited good physical characteristics, including a slightly opaque white color, a distinctive lemongrass aroma, a liquid texture that absorbs easily into the skin, and visual homogeneity. pH and viscosity tests showed significant differences between formulations, but all remained within safe ranges. Irritation tests showed that all formulations are safe for use as they did not cause negative reactions on the volunteers' skin. Based on hedonic testing, the formulation with a 20% concentration was most preferred by panelists in terms of aroma and color. Antibacterial activity testing showed that all concentrations (10%, 20%, and 30%) were able to inhibit the growth of Propionibacterium acnes, with effectiveness increasing as the concentration increased. The 10% formulation already demonstrated moderate antibacterial activity, while the 20% and 30% formulations fall into the strong category. Therefore, the lemongrass essential oil toner is effective and safe for use as an acne treatment, with an optimal concentration of 20%.